A IDEIA DE FORMAÇÃO CULTURAL (BILDUNG) NO JOVEM-NIETZSCHE ENQUANTO PRÁTICA DIDÁTICA DO FILOSOFAR: REFLEXÕES PARA O PROFESSOR DE ENSINO MÉDIO DE ESCOLA PÚBLICA - Wellington dos Santos (2021)
In this dissertation we seek to build a pedagogical and philosophical itinerary in the works of the so-called 'young-Nietzsche' whose objective is to diagnose and propose his way of philosophizing called genealogy as a possible teaching method for the philosophy teacher in public high school; we also critically compare the skill sets and competences required through official documents to this professional in contrast to the understanding of Education for Nietzsche expressed by the concept of Cultural Formation (Bildung). Thus, our interpretation based on literature review and document analysis identifies that such method in the 'young-Nietzsche' is structured along two paths: aesthetic education (sensitivity formation) and philosophical education (evaluation and critical interpretation of values). Keywords: young-Nietzsche; cultural formation; method; genealogy.